A Newyork Kávéház vezetősége 1920-1936 között - Czina, Sara (Közép-Európai Közlemények, 2023)
The purpose of the study: To examine how the Newyork Coffeehouse was run between 1920 and 1936. What were Vilmos Tarján’s, the executive board member and main shareholder’s, business policies? What profile did he intend for the Coffeehouse? In this period, between the two World Wars the Coffeehouses were struggling with the circumstances. What were the Coffeehouse’s solutions for the post-World War challenges and the problems of the Great Depression? Applied methods: To get to know the Newyork Coffeehouse Company Limited, the sources were the documents of the Company Registry. These helped to reconstruct the list of the shareholders. The balance and profit loss accounts were used to examine the profitability of the Coffeehouse. The problems of the Coffeehouses in Budapest between 1920 and 1936 were examined through the articles of professional journals. Finally, to understand Vilmos Tarján’s aspirations, his own books and articles of the daily newspapers were used. Outcomes: Vilmos Tarján wanted to turn the Newyork Coffeehouse into a luxurious, high-end Coffeehouse. In order to reach this goal, he renovated the interior, later refurbished and modernized it several times. In addition, he established one of the best kitchens in the city and engaged the audience with frequent performances and concerts. With these aspirations, he could solve the post-World War problems successfully. However, his skills and role in the associations of the industry were not enough to face the challenges that arose during the Great Depression.